Istighātha Dhikr Practices Toward Human Well-Being: An Implication for Islamic Education - Sholihah, Ni'matus; Kusaeri; Kholis, Nur; Muntafi’ah, Umi; Huriyah, Lilik (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
Istighātha dhikr is a spiritual practice performed by seeking help, protection, and forgiveness from Allah. It is a process of seeking Allah's assistance and protection against all weaknesses, sins, and mistakes committed. However, this practice has been carried out in various ways in different countries. This research aims to evaluate how the practice of istighātha dhikr in various countries can be implemented to improve well-being. Out of 151 identified articles, 14 relevant articles were found based on inclusion and exclusion criteria such as document type, source, and period. PRISMA was used as a guideline for selecting articles in this research. Google Scholar, EBSCO, and Publish or Perish were used as literature search databases. VOSviewer was used to analyze publication data and collaboration networks. This article provides an overview of the practice of istighātha dhikr in various countries. The results of this study indicate that istighātha dhikr is not only a practice for spiritual development but also has significant impacts in strengthening religious identity, improving the quality of worship, increasing spiritual awareness, enhancing spiritual, physical, and mental aspects, and improving overall well-being.